السودان.. من البشير الى البرهان و حمدوك - محطات صعبة و تحديات ماثلة - Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي (Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي, 2023)
The peaceful youth popular movement in Sudan, which began in the form of protests and a direct exit to the street, is one of the strongest manifestations of opposition action, and one of the biggest challenges faced by the rescue regime led by ousted President Omar al-Bashir since he took power in 1989, until the date of the start of the protests in the third week of December 2018. | يعد الحراك الشعبي الشبابي السلمي في السودان الذي بدأ في صورة احتجاجات و خروج مباشر للشارع من أقوى مظاهر الفعل المعارض, و من اكبر التحديات التي واجهها نظام الانقاذ بقيادة الرئيس المخلوع عمر البشير منذ توليه السلطة في عام 1989م, حتى تاريخ انطلاق الاحتجاجات في الاسبوع الثالث من ديسمبر 2018م.